Interpretation of p16, p53 and mismatch repair protein immunohistochemistry in gynaecological neoplasia. Issue 6 (June 2020) - Wing-Cheuk Wong, Richard; Palicelli, Andrea; Hoang, Lien; Singh, Naveena
Abstract: Current management of gynaecological neoplasms is underpinned by their molecular characteristics. For many neoplasms the underlying genetic abnormalities can be reliably detected using immunohistochemistry for protein expression as a surrogate. The three most widely utilized biomarkers in this regard in gynaecological neoplasms are p16, p53 and mismatch repair (MMR) proteins, and it is vital for all pathologists to be aware of the indications for their use, correct interpretation of expression patterns, awareness of technical and interpretive pitfalls as well as appropriate reporting terminology.